Design of a gait acquisition and analysis system for assessing the recovery in a classical murine model of Parkinson's disease - Damale, Pranav, author; Chong, Edwin K. P., advisor; Tjalkens, Ronald, committee member; Ebert-Uphoff, Imme, committee member (Colorado State University. Libraries, 2015)
Gait deficits are important clinical symptoms of Parkinson's disease (PD). Data focusing on gait can be used to measure recovery of motor impairments in rodents with systemic dopamine depletion. This thesis presents a design for a gait acquisition and analysis system able to capture paw strikes of a mouse, extract their positions and timing data, and report quantitative gait metrics to the operator. These metrics can then be used to evaluate the gait changes in mice. This work presents the design evaluation of the system, from initial cellphone captured video concepts through prototyping and testing to the final implementation. The system utilizes a GoPro camera, optimally lit walkway design, image processing techniques to capture footfalls, and algorithms for their quantitative assessment. The results gained from live animal study with methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced murine model of PD and treated with 1,1-bis(3'-indolyl)-1-(p-chlorophenyl)methane (C-DIM12) are presented, and it is shown how the quantitative measurements can be used to determine healthy, injured, and recovering gait.
Keywords: C-DIM 12; image processing; mouse gait; MPTP; object detection; Parkinson's disease